(Dis)regarding the contemporary Church as the peacemaker in Zimbabwe - Tagwirei, Kimion (Verbum et ecclesia, 2025)
It is life-bearing to sustain the condition and place of the Church as the salt, light and conscience of the Church in society. Contemporaneously, in the Zimbabwean context of tragic political and socio-economic conflict, the Church appears to be ineffective at fostering peace, healing and reconciliation, mainly because of corruption, state capture, factionalism and a passive approach to addressing national crises. However, disregarding the Church in peacebuilding dismisses the possible role of the remnant in national development. Meanwhile, court prophets have annexed the position of the Church in politics by prophesying selfish elitist desires at the expense of the entire nation. Thus, discarding the conciliatory role of the Church disables national transformation. Employing data from purposively sampled in-depth interviews and literature through a lens of remnant theology, this study found that destructive selfishness, conflict, disunity and other problems continue to taint the ecclesial image in Zimbabwe. How can the remnant restore the conscience of the Church for it to regain public respect, trust and its position as the peacebuilding conscience of society in Zimbabwe? This study explores restorative strategies and concludes that to save crisis-stricken Zimbabwe, the remnant should rebuild an other-centred consciousness and transformative capacity, preach and embody peace.Intradisciplinary and/or interdisciplinary implicationsThis study links ecclesiology with peace studies, politics and sociology to troubleshoot national transformation in Zimbabwe.